RECRUITMENT MANAGEMENT OF EDUCATORS AT THE STATE ELEMENTARY SCHOOL OF SINDUADI 1 SLEMAN YOGYAKARTA - Heni Nurhayanti; Ismi Fadila (Universitas Sebelas Maret, 2018)
The quality of human resources is very influential on the achievement of school vision and mission. Determination of the quality of human resources in schools can be known from the recruitment management of educators. Therefore the purpose of this study is to know the recruitment management of educators in SDN Sinduadi 1. The research method used is qualitative descriptive. The results show that schools perform the required job analysis, determine recruitment strategies such as announcement of new teacher vacancies within the internal scope and use appropriate sources, techniques and recruitment methods. Implementation of recruitment, this school never made an announcement in the mass media only dilingkup internal to the teacher staff. Selection is done by the principal by way of file selection and then followed by interview. After that, the principal decides who the teacher will receive. The conclusion of this research is the management of recruitment of educator at SDN Sinduadi 1 is still less coordinated.